Unexpected increase of aortic stiffness in juvenile Spondyloarthropathies. (17th December 2020) - Dedeoglu, Reyhan; Yildiz, Mehmet; Karagozlu, Fatih; Oztunc, Funda; Ulug, Nujin; Akdeniz, Beste; Adrovic, Amra; Haslak, Fatih; Sahin, Sezgin; Barut, Kenan; Kasapcopur, Ozgur
Abstract: Juvenile spondyloarthropathy is an umbrella term for a group of childhood rheumatic diseases that can cause chronic arthritis extending to the axial skeleton before the age of 16. Although ankylosing spondylitis has aortic involvement as one of its most important effects, this relationship has not been extensively studied in children with juvenile spondyloarthropathy. Here, a cross-sectional study of the elastic properties of the aorta of 43 patients with juvenile spondyloarthropathy and 19 healthy controls is reported. Aortic stiffness assessed by echocardiography was used to predict the presence of aortitis, supplemented by pulsed-wave tissue Doppler indices. The right ventricular fractional area change was found to be significantly lower in the patients with juvenile spondyloarthropathy than in the healthy controls; aortic strain and distensibility were also significantly lower, and aortic stiffness index β was significantly higher; and the aortic root diameter change was significantly lower. According to HLA-B27 positivity, there was no difference in the stiffness parameters between the two groups. There was a significant correlation between juvenile Ankylosing Spondylitis Disease Activity Index and aortic diameter change, between juvenile Ankylosing Spondylitis Disease Activity Index and aortic stiffness. Thus, juvenile spondyloarthropathy is linked to high aortic stiffness parameters.